Nutritional Status and Nutritional Knowledge of Malay Pregnant Women in Selected Private Hospitals in Klang Valley - Zahara Abdul Manaf,; Nuruljannah Johari,; Lee, Yee Mei; Ng, Sim Yee; Chua, Kai Yin; Loke, Wai Teng (penerbit ukm, 2014)
Adequate nutrition is important for mothers and their offspring during and after birth. This cross sectional study was conducted to determine nutritional status and nutritional knowledge of pregnant women from two selected private hospitals in Klang Valley, Malaysia. A total of 236 Malay pregnant women aged between 20 to 45 years old (mean age 31+5 years) were recruited through convenient sampling method. Socio-demographic data, nutritional knowledge and a 24-hours diet recall were obtained through a self-administered questionnaire. Anthropometric and haemoglobin data were obtained from the antenatal records in the respective hospitals. The percentages of participants who were underweight, normal, overweight and obese before pregnancy were 12.7%, 55.1%, 25.0% and 7.2% respectively. Among those who were obese before pregnancy, a total of 59.7% had inadequate weight gain, 24.6% gained adequate weight and 15.7% gained excessive gestational weight. About 33.5% of subjects were anaemic (Hb < 11.0g/dL). The mean daily energy intake of the participants was 1748 ± 526 kcal which was 76% of RNI. Calcium (73% of RNI), folic acid (36% of RNI), niacin (89% of RNI) and vitamin D (40% of RNI). The nutritional knowledge level of subjects was moderate (51.9 ± 13.8%). Lower monthly household income (p < 0.001), educational level (p < 0.001) and gestational stage (p < 0.05) of participants were associated with a lower nutritional knowledge level. Nutritional knowledge score was positively correlated with gestational weight gain (r = 0.166, p < 0.05) and haemoglobin level (r = 0.200, p < 0.05). Subjects who claimed practising food taboos had higher nutritional knowledge score (54.9 ± 12.5%) than those who did not (49.9 ± 14.4%)(p < 0.05). A comprehensive nutrition education should be integrated in the antenatal classes to improve nutritional status of pregnant women.